2021
DOI: 10.3389/fphar.2021.710778
|View full text |Cite|
|
Sign up to set email alerts
|

Remdesivir Strongly Binds to RNA-Dependent RNA Polymerase, Membrane Protein, and Main Protease of SARS-CoV-2: Indication From Molecular Modeling and Simulations

Abstract: Development of new drugs is a time-taking and expensive process. Comprehensive efforts are being made globally toward the search of therapeutics against SARS-CoV-2. Several drugs such as remdesivir, favipiravir, ritonavir, and lopinavir have been included in the treatment regimen and shown effective results in several cases. Among the existing broad-spectrum antiviral drugs, remdesivir is found to be more effective against SARS-CoV-2. Remdesivir has broad-spectrum antiviral action against many single-stranded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 60 publications
0
22
0
2
Order By: Relevance
“…Targets for remdesivir also include membrane protein (M protein) and RDRP inhibitors. It is the first drug approved clinically and repurposed as a potent antiviral agent for treating SARS-CoV-2 infected patients [ 76 , 77 ]. A well-recognized host protease inhibitor, including camostat mesylate and nafamostat, was useful in inhibiting the host TMPRSS-2 protease that restricts the entry of SARS-CoV-2 viruses into target host cells [ 78 ].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Targets for remdesivir also include membrane protein (M protein) and RDRP inhibitors. It is the first drug approved clinically and repurposed as a potent antiviral agent for treating SARS-CoV-2 infected patients [ 76 , 77 ]. A well-recognized host protease inhibitor, including camostat mesylate and nafamostat, was useful in inhibiting the host TMPRSS-2 protease that restricts the entry of SARS-CoV-2 viruses into target host cells [ 78 ].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…The residues of the SARS-CoV-2 main protease (nsp5) involved in binding for remdesivir and Paxlovid (two antivirals recommended by the WHO for COVID-19 treatment in patients at risk of hospital admission) were highly conserved in our sequence dataset, with a percentage of mutated sequences below 0.2%. Some of these residues are involved in the binding of both drugs (C145, E166, H163, H164, Q192), while G143 is involved in Paxlovid binding, and other sites interact with remdesivir (H41, M49, Y54, F140, N142, S144, M165, L167, P168, H172, N187, R188, Q189, T190, and A191) [ 110 , 111 ]. We only found one sequence with a deletion in residue 192 (involved in the binding of both drugs) and no other aa changes in the rest of the sites that interact with Paxlovid, which showed complete conservation among the whole Spanish sequence dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several inhibitors and their mode of action have been demonstrated ( Khan et al, 2021c ; Rani et al, 2021 ). Edwards et al found that the spike protein samples kept at diverse temperatures did not show any considerable denaturation, while they observed an increase in upper molecular weight bands in a sample that was kept at 37°C ( Edwards et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%